The changes in Blood Pressure in Patients Undergoing Spinal Anesthesia According to the Size of Spinal Needle (G22 versus G24): Case Reference Study - Ahmed Matrood Kadhim1 , Salman Abbas Badi 1, Watheq Maeh Naji1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Previous studies of patients with spinal anesthesia prior to sympathectomy revealed that vasodilatation and hypotension, with subsequent reduction in arterial pressure, were the most common side effects (observed in more than 30% of patients). Hypotension in epidural anesthesia was stated to be more gradual and less extreme than in spinal anesthesia when a comparable amount of anesthesia was given. Aim of the study: In the current study, we are aiming to evaluate the effect of different size of spinal needle on development of possible blood pressure changes throughout the spinal anesthesia procedure. Patients and Methods: The current observational case reference study was carried out at Al-Diwaniyah Teaching Hospital in Al-Diwaniyah Province, Iraq. The beginning of the study is dated back to the 3rd of April 2018 and the study continued till September the 15th 2019. It included 60 patients undergoing spinal anesthesia for various surgical operations. In 30 patients a spinal needle of 22 gauge was used whereas in the second group (n = 30), a spinal needle of gauge 24 was used. All patients were instructed to be nil by mouth overnight. Results: In group 1 (22G), mean systolic blood pressure showed gradual reduction, 139.00 ±8.35 mmHG, 120.67 ±11.43 mmHg, 106.00 ±11.02 mmHG and 97.33 ±10.15 mmHg; similarly, in group 2 (24G) mean systolic blood pressure showed gradual reduction, 144.00 ±10.37 mmHG, 138.00 ± 7.61 mmHg, 131.33 ±9.00 mmHG and 131.67 ±11.40 mmHg; however, the rate of reduction in group 2 (G24) was less than that seen in case of group 1 (G22). In group 1 (22G), mean diastolic blood pressure showed gradual reduction, 84.00 ±7.24 mmHG, 72.00 ±6.64 mmHg, 61.33 ±9.73 mmHG and 54.00 ±8.94 mmHg; similarly, in group 2 (24G) mean diastolic blood pressure showed gradual reduction, 87.33 ±7.85 mmHG, 81.33 ±7.30 mmHg, 77.33 ±10.15 mmHG and 78.00 ±5.51 mmHg; however, the rate of reduction in group 2 (G24) was less than that seen in case of group 1 (G22). Conclusion: It appears that the use of narrower spinal needle is recommended as it is associated with significantly less drop in both systolic and diastolic blood pressure, thus less hemodynamic disturbances in patients undergoing spinal anesthesia for various indications